ANALISIS KEMAMPUAN BERPIKIR KRITIS DI TINJAU DARI MINAT BELAJAR MATEMATIKA SISWA SELAMA PANDEMI - Larasanti Hasibuan; Rahmatika Elindra; Sinar Depi Harahap (JURNAL MathEdu (Mathematic Education Journal), 2022)
The aim of the research is to analyze critical thinking ability in terms of students’ learning interest during Covid – 19 period in SMP Negeri 3 Satu Atap Andam Dewi. The approach of the research is descriptive qualitative. Subject of the research consist of 10 students. Observation, test, questionnaire, and interview were used in collecting the data and triangulation technique was used in analysis technique. The research of the research shows the average of students’ learning interest is 78.95 (good category) which 50% of students in very good category, 30% of students in good category, and 20% in enough category. Furthermore, the average of students’ critical thinking ability is 52.24 (medium category). It’s concluded students’ able to analysis the questions, evaluate by using directly strategy in solving the questiona, and taking conclution.